PENGARUH DISIPLIN KERJA DAN PROSEDUR KERJA DALAM MEMPENGARUHI KINERJA PERANGKAT DESA MELALUI PRODUKTIVITAS KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus di Kantor Desa Mojosari, Desa Kertosari, Desa Awar-awar, Desa Parante, Kecamatan Asembagus Kabupate - Malaysia, Hamzah Malik; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The research objective was to determine the effect of work discipline and work procedures in influencing employee performance through work productivity as an intervening variable (a case study in the Mojosari Village Office, Kertosari Village, Awar-awar Village, Paraante Village, Asembagus District, Situbo Regency. The sampling technique used in this study is a saturated sample with a sample size of 60 employees.Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that work discipline has a positive and significant effect on work productivity, work procedures have a positive and significant effect on work productivity Work discipline has a positive and significant effect on employee performance, work procedures have a negative but significant effect on performance employees, work productivity has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance through work productivity, work procedures have a positive and significant effect on employee performance through work productivity